Spektrum: Kebesaran Gayo dalam Pentas Seajarah - Madjid, M. Dien (Buletin Al-Turas, 2010)
Gayo people's role in national history during Dutch colonization is very significant. The exposure of their role will surely uplift the sense of natioÂnalism and patriotism of Gayo people toward IndoÂnesia. Since every region has its own history, it is suggested that: 1) there is a research of the history of Gayo/Linge which later become the regency of Aceh Tengah; 2) the local government should seek to enhance the prestige and dignity of Takengon in the eyes of nation in form of proposing Gayo's pioneer of independence hero; 3) the local people and goÂvernment should seek, nurture, and maintain the heritages of Gayo ranging from the mythical /legendary to the archaeological objects that were collected in the form of sites and museums.